IJAR 2019
DOI: 10.21474/ijar01/8617
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Ziziphus Joazeiro Peel for Indigo Blue Adsorption.

Abstract: The Zizyphus joazeiro Mart peel (ZJP) was evaluated to remove the indigo blue (IB) in aqueous medium through the adsorption process. The high value of the maximum adsorptive capacity (50 mg.g -1 ) of ZJP for this textile dye proves that this natural adsorbent is efficient in IB adsorption. Tests on glass columns support this claim. ZJP was more efficient (90.5%) than activated carbon (15.2%) in the removal of IB present in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…Raymundo et al [6] also observed similar results, which were achieved when sugar cane bagasse was used to adsorb Congo Red. Ribeiro et al [24] also noticed that adsorption of Indigo Blue by Ziziphus joazeiro peel showed desorption events as mechanical agitation time increased.…”
Section: Mechanical Agitation Timementioning
confidence: 96%
See 2 more Smart Citations
“…Raymundo et al [6] also observed similar results, which were achieved when sugar cane bagasse was used to adsorb Congo Red. Ribeiro et al [24] also noticed that adsorption of Indigo Blue by Ziziphus joazeiro peel showed desorption events as mechanical agitation time increased.…”
Section: Mechanical Agitation Timementioning
confidence: 96%
“…They demonstrated that 2.0 g of this adsor-bent were able to remove 90% and 89% of Congo Red (25 mg•L −1 ) and Indigo Blue (1000 mg•L −1 ), respectively. Ribeiro et al [24] demonstrated that 1.5 g of Zizyphus joazeiro Mart peel removed approximately 84% of Indigo Blue (1000 mg•L −1 ) from aqueous medium.…”
Section: Vermicompost Massmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into consideration the generated problems by the dyes, technologies that can remove it from water are extremely important. Several of those techniques have been studied, such as biodegradation (Manimekalai and Swaminathan, 2000), photodegradation (Giraldo and Restrepo, 2004), ozone treatment (Kunz et al, 1999) and the adsorption process (Carneiro et al, 2019;Ribeiro et al, 2019). The latter method being the focus of this work.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption processes, using natural adsorbents, provide satisfactory results when used for the removal of different type of dyes (Brito et al, 2010). Some studies have already been performed using natural adsorbents, as in the case of the use of Brazil nut husk for the removal of methylene blue and indigo carmine dyes (Brito et al, 2010), in the use of sugar-cane bagasse for the treatment of water containing congo red (Raymundo et al, 2010), in the use of vermicompost for congo red and indigo blue dyes removal , in the use of Ziziphus Joazeiro pell for indigo blue adsorption (Ribeiro et al, 2019), and others (Gupta, 2009). Within this scenario would be black jurema bark powder (BJBP) a new alternative for dyes effluents treatment?…”
Section: Introductionmentioning
confidence: 99%